Stimulus-specificity in the responses of immune sentinel cells. Issue 18 (December 2019) - Sheu, Katherine M.; Luecke, Stefanie; Hoffmann, Alexander
Abstract: Innate immune sentinel cells must initiate and orchestrate appropriate immune responses for myriad pathogens. These stimulus-specific gene expression responses are mediated by combinatorial and temporal coding within a handful of immune response signaling pathways. We outline the scope of our current understanding and indicate pressing outstanding questions. Highlights: Innate immune sentinel cells produce stimulus-specific gene expression programs. Stimuli are encoded in combinations and temporal patterns of signaling activity. How response genes decode combinatorial and temporal activity is a research focus. The capacity of cells for stimulus-specific responses has not been quantified. How the tissue microenvironment affects coding capacities is of great interest.